The perceived level of job satisfaction among the graduates of Bachelor of Science in Tourism, Hotel, and Travel Industry Management of their chosen career - Calleja,Markus Jerico B. Gonzales, Cris Angelo R. Reyes,Kevin Joshua D. Sabala,Trisha Mae C. Vidal, Jemcy May F. and Villanueva, Laarnie Marie O. 4 0 16; 5 (2013)
u
Undergraduate Thesis: (BS in Travel and Tourism Management)- Pamantasan ng Lungsod ng Maynila 2013.
Keywords: 2 -- 0; 6; 20; 20; 2